The transformation of political community : ethical foundations of the Post-Westphalian era - Linklater, Andrew (Polity Press, 2004)
Anarchy, community and critical international theory. The critique of neo-realism. The problem of community in international relations. The changing context of the modern state. Theorising the reconfiguration of political community -- Universality, differ